Parents' perspective on childhood vaccines and the correlation of vaccine hesitancy with health literacy - Onen, Cihan; Ustundag Ocal, Nursel (Progress in Nutrition, 2022)
Study Objectives: The purpose of this study was to analyze the parents' perspective on childhood vaccinations and the correlation between vaccine hesitancy the health literacy. Methods: The population of this cross-sectional study consists of the parents of the pediatric patients who receive service from the Pediatric Clinic of the Yüksek İhtisas Training and Research Hospital in Bursa, Turkey. Personal Information Form, Vaccine Hesitancy Scale, and Turkey Health Literacy Scale-32 (TSOY-32) tools were used to collect data. Results: 78% of the parents being the majority think that unvaccinated children are a threat to their children, 68.8% of them think childhood vaccines are beneficial and 67.1% of them think that mandatory vaccines are necessary. Parents who do not find vaccines helpful are most likely to view the flu vaccine negatively. Families oppose the flu vaccine due to the fact that there are many types of flu vaccines, they are not useful and they are unreliable. The vaccine hesitancy mean score of the participants was calculated as 22.29 and the mean score of TSOY-32 was calculated as 30.39. There is a weak, negative (rspearman=-0.211), and significant (p=0.005) relationship between vaccine hesitancy and health literacy. Conclusion: It has been observed in this study that a substantial number of parents are against childhood vaccines. Unfounded posts on non-scientific channels such as social media become determinative in parents' negative views of vaccines. This situation can be life-threatening to children. Vaccine hesitancy, albeit weakly, also decreases with the increase in health literacy.